The case of the ECB: Better to lean against the wind than to fight a hurricane - Christian Drescher (Intereconomics, 2011)
In the light of the recent financial crisis, the ECB has announced a slight shift in the reading of its monetary policy strategy and acknowledges that the case for a 'leaning against the wind' strategy has strengthened. This implies that now, more than ever, the ECB is willing to dampen asset bubbles in the early stage of their formation. This article explains what the ECB can learn from historical asset bubbles in EU eurozone member countries. The empirical analysis indicates that asset bubbles in some member countries are mostly followed by asset bubbles in further member countries, which supports the ECB's current reading of its monetary policy strategy.
Keywords: 330